Cement-containing composition, and method of repairing pavement

JP2025030404APending Publication Date: 2025-03-07EAST JAPAN RAILWAY COMPANY +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023135677
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0008】 本発明のセメント含有組成物は、硬化後には優れた吸水性を有するため、降雨等による水が該セメント含有組成物の硬化体に吸収されて、該セメント含有組成物を用いた舗装体表面の水溜りの発生を起こりにくくすることができる。 また、本発明のセメント含有組成物は、硬化前の流動性に優れているため、コテ等を用いた施行時の作業性に優れている。 また、本発明のセメント含有組成物は、付着性に優れているため、舗装体(特に、密粒度アスファルト混合物を用いた舗装体)の補修に好適である。 さらに、本発明のセメント含有組成物の硬化体は耐摩耗性に優れているため、舗装体の少なくとも一部として使用しても、人の歩行等に十分に耐えることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025030404000001
    Figure 2025030404000001
  • Figure 2025030404000002
    Figure 2025030404000002
  • Figure 2025030404000003
    Figure 2025030404000003
Patent Text Reader

Abstract

To provide a cement-containing composition excellent in pre-hardening fluidity, adhesiveness, post-hardening abrasion resistance and water absorption.SOLUTION: In a cement-containing composition including cement, inorganic porous particles, fine aggregate, a polymer for cement admixture and water, the inorganic porous particles have a particle size distribution in which the content of particles of a particle size of 0.5 mm or more and smaller than 1.0 mm is 40 to 60 mass% and the content of particles of a particle size of 1.0 to 2.0 mm is 40 to 60 mass%, with the amount of the inorganic porous particles being 150 to 420 pts.mass, the amount of the fine aggregate being 180 to 320 pts.mass, the amount of the polymer for cement admixture being 18 to 62 pts.mass, and the amount of water being 170 to 300 pts.mass, relative to 100 pts.mass of cement.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cement-containing composition and a method for repairing a pavement using the cement-containing composition. [Background technology]

[0002] Conventionally, quick-release repair materials such as heated asphalt mortar, asphalt emulsion-based repair mortar, resin-based repair mortar, and polymer cement-based mortar have been known as materials for repairing depressions in pavement surfaces that use dense-graded asphalt mixtures or the like, which have been caused by wear, surface peeling, deterioration, or thermal flow. Patent Document 1 describes a composition for forming pavement surfaces, which contains a polymer emulsion for admixture with cement, cement, and silica sand, and is characterized in that the proportion of silica sand having a particle size of 0.6 mm or less in the total amount of the silica sand is 20 to 100 mass %, the amount of the cement is 75 to 130 mass parts per 100 parts by mass of the polymer emulsion for admixture with cement, the proportion of polymer in the polymer emulsion for admixture with cement is 35 to 55 mass %, and the amount of the silica sand is 250 to 1,700 mass parts per 100 parts by mass of the polymer emulsion for admixture with cement. Patent Document 2 also describes a repair method for when the concrete slab located below the asphalt pavement has deteriorated, which uses a polymer cement mortar to fill a cavity formed in the concrete slab, containing rapid hardening cement, a polymer for cement, fine aggregate and water, and having a unit polymer amount of 50 to 150 kg / m 3 The paper describes a polymer cement mortar having a water-cement ratio of 26 to 35% and a polymer cement ratio of 10 to 30%. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6466701 [Patent Document 2] JP 2013-234489 A Summary of the Invention [Problem to be solved by the invention]

[0004] Many of the pavements such as the floors of station platforms are made of dense-graded asphalt mixtures. When depressions appear on the surface of the pavement due to wear, surface peeling, deterioration, thermal flow, etc., water accumulates in the depressions when it rains, causing problems such as water splashes on users (passersby) and soiling their shoes. Even if pavement is repaired using standard repair materials, the pavement surface will not become smooth, and slight unevenness will remain, resulting in problems such as water pooling in and around the repaired areas. In addition, pavement with a small slope has a problem in that water does not flow easily, so water pools in the area. An object of the present invention is to provide a cement-containing composition which has excellent fluidity and adhesiveness before hardening, and excellent abrasion resistance and water absorbency after hardening. [Means for solving the problem]

[0005] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned objects can be achieved by a cement-containing composition comprising cement, inorganic porous particles having a particle size distribution in which the content of particles having a particle size of 0.5 mm or more and less than 1.0 mm is 40 to 60 mass % and the content of particles having a particle size of 1.0 to 2.0 mm is 40 to 60 mass %, fine aggregate, a polymer for admixture with cement, and water, in which the amount of the inorganic porous particles is 150 to 420 mass parts, the amount of the fine aggregate is 180 to 320 mass parts, the amount of the polymer for admixture with cement is 18 to 62 mass parts, and the amount of the water is 170 to 300 mass parts per 100 mass parts of cement, and have completed the present invention. That is, the present invention provides the following [1] to [7]. [1] A cement-containing composition comprising cement, inorganic porous particles, fine aggregate, a polymer for admixture with cement, and water, wherein the inorganic porous particles have a particle size distribution in which the content of particles having a particle size of 0.5 mm or more and less than 1.0 mm is 40 to 60 mass %, and the content of particles having a particle size of 1.0 to 2.0 mm is 40 to 60 mass %, and the cement-containing composition is characterized in that, relative to 100 mass parts of the cement, the amount of the inorganic porous particles is 150 to 420 mass parts, the amount of the fine aggregate is 180 to 320 mass parts, the amount of the polymer for admixture with cement is 18 to 62 mass parts, and the amount of the water is 170 to 300 mass parts.

[0006] [2] The cement-containing composition according to [1], wherein the inorganic porous particles are zeolite. [3] The cement-containing composition according to [1] or [2], wherein the fine aggregate has a particle size distribution in which the content of particles having a particle size of 0.15 to 0.6 mm is 90 mass% or more. [4] The cement-containing composition according to any one of [1] to [3], wherein the polymer for cement admixture is at least one selected from the group consisting of acrylic polymers and styrene-acrylic polymers. [5] The cement-containing composition according to any one of [1] to [4], wherein the water absorption rate of a hardened product of the cement-containing composition is 25.0% or more.

[0007] [6] A pavement comprising a hardened product of the cement-containing composition according to any one of [1] to [5] above and a hardened product of a dense-graded asphalt mixture. [7] A method for repairing a pavement using the cement-containing composition described in any one of [1] to [5] above, comprising: a powdery composition preparation step of mixing the cement, the inorganic porous particles, and the fine aggregate to obtain a powdery composition; a cement-containing composition preparation step of mixing the powdery composition, the polymer for admixture with cement, and the water to prepare the cement-containing composition; and a filling step of filling a recess in a pavement that requires repair and contains a hardened body of a dense-graded asphalt mixture with the cement-containing composition and hardening the composition. Effect of the Invention

[0008] Since the cement-containing composition of the present invention has excellent water absorption properties after hardening, water from rainfall, etc. is absorbed into the hardened body of the cement-containing composition, making it possible to prevent puddles from forming on the surface of a pavement using the cement-containing composition. Furthermore, the cement-containing composition of the present invention has excellent fluidity before hardening, and therefore has excellent workability when applied using a trowel or the like. Furthermore, the cement-containing composition of the present invention has excellent adhesion and is therefore suitable for repairing pavements (particularly pavements using dense-graded asphalt mixtures). Furthermore, the hardened product of the cement-containing composition of the present invention has excellent abrasion resistance, and therefore can fully withstand foot traffic, etc., even when used as at least a part of a pavement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The cement-containing composition of the present invention is a cement-containing composition containing cement, inorganic porous particles, fine aggregate, a polymer for admixture with cement, and water, in which the inorganic porous particles have a particle size distribution in which the content of particles having a particle size of 0.5 mm or more and less than 1.0 mm is 40 to 60 mass %, and the content of particles having a particle size of 1.0 to 2.0 mm is 40 to 60 mass %, and the amount of the inorganic porous particles is 150 to 420 mass parts, the amount of the fine aggregate is 180 to 320 mass parts, the amount of the polymer for admixture with cement is 18 to 62 mass parts, and the amount of the water is 170 to 300 mass parts relative to 100 mass parts of cement. The details are explained below.

[0010] Examples of cements that can be used in the present invention include (i) ultra-fast hardening cement (also called rapid hardening cement), (ii) various Portland cements such as ordinary Portland cement, early strength Portland cement, ultra-early strength Portland cement, moderate heat Portland cement, and low heat Portland cement, and (iii) mixed cements such as blast furnace cement and fly ash cement. These may be used alone or in combination of two or more. Among these, from the viewpoint of early opening to traffic, ultra-rapid-hardening cement, ultra-early-strength Portland cement, and early-strength Portland cement are preferred, ultra-rapid-hardening cement and ultra-early-strength Portland cement are more preferred, and ultra-rapid-hardening cement is particularly preferred.

[0011] The inorganic porous particles used in the present invention have a particle size distribution in which the content of particles having a particle size (grain size) of 0.5 mm or more and less than 1.0 mm is 40 to 60 mass % (preferably 42 to 58 mass %, more preferably 45 to 55 mass %) and the content of particles having a particle size of 1.0 to 2.0 mm is 40 to 60 mass % (preferably 42 to 58 mass %, more preferably 45 to 55 mass %), from the viewpoint of further improving the water absorption of the hardened body of the cement-containing composition and further improving the fluidity before hardening. From the viewpoint of further improving the fluidity of the cement-containing composition before hardening, the content of particles having a particle size of less than 0.5 mm in the inorganic porous particles is preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 3% by mass or less. From the viewpoint of further improving the water absorption of the hardened body of the cement-containing composition, the content of particles having a particle size of more than 2.0 mm in the inorganic porous particles is preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 3% by mass or less. In this specification, the particle size (particle size) means a size corresponding to the size of the openings of a sieve. For example, a particle size of 0.5 mm or more means that the particle will not pass through a sieve with an opening of 0.5 mm.

[0012] Examples of inorganic porous particles include zeolite, diatomaceous earth, sepiolite, volcanic ash, siliceous shale, pumice, etc. These may be used alone or in combination of two or more. Among these, from the viewpoint of increasing the water absorption capacity of the hardened body of the cement-containing composition and further improving the fluidity before hardening, zeolite and diatomaceous earth are preferred, and zeolite is more preferred. In order to make the inorganic porous particles have the above-mentioned particle size distribution, the inorganic porous particles may be appropriately subjected to granulation, firing, etc.

[0013] The amount of inorganic porous particles per 100 parts by mass of cement is 150 parts by mass or more, preferably 160 parts by mass or more, more preferably 180 parts by mass or more, even more preferably 200 parts by mass or more, even more preferably 250 parts by mass or more, even more preferably 300 parts by mass or more, and particularly preferably 350 parts by mass or more, from the viewpoint of further improving the water absorption of the hardened body of the cement-containing composition. Also, the above amount is 420 parts by mass or less, preferably 410 parts by mass or less, more preferably 380 parts by mass or less, and particularly preferably 330 parts by mass or less, from the viewpoint of further improving the wear resistance of the hardened body of the cement-containing composition.

[0014] The fine aggregate used in the present invention preferably has a particle size distribution in which the content of granules (particles) having a particle size (grain size) of 0.15 to 0.6 mm is 90 mass% or more (preferably 95 mass% or more, more preferably 100 mass%), from the viewpoint of improving the fluidity of the cement-containing composition before hardening and the water absorption and abrasion resistance of the hardened body of the cement-containing composition. In addition, from the viewpoint of increasing the water absorption capacity of the hardened body of the cement-containing composition and further improving the fluidity before hardening, the content of particles having a particle size of less than 0.15 mm in the fine aggregate is preferably less than 10 mass%, more preferably 5 mass% or less, and particularly preferably 3 mass% or less. Furthermore, from the viewpoint of further improving the abrasion resistance of the hardened body of the cement-containing composition and further suppressing material separation, the content of particles having a particle size exceeding 0.6 mm in the fine aggregate is preferably less than 10 mass%, more preferably 5 mass% or less, and particularly preferably 3 mass% or less.

[0015] Examples of fine aggregates include silica sand, river sand, mountain sand, land sand, sea sand, crushed sand, slag fine aggregate, and lightweight fine aggregate. These may be used alone or in combination of two or more. Among them, silica sand is preferred from the viewpoints of improving the wear resistance of the hardened body of the cement-containing composition and ease of availability. Moreover, from the viewpoint of ease of preparation of a premix product by mixing with other materials, a dry fine aggregate (for example, dry silica sand) is preferred. The amount of fine aggregate per 100 parts by mass of cement is 180 parts by mass or more, preferably 190 parts by mass or more, more preferably 220 parts by mass or more, and particularly preferably 240 parts by mass or more, from the viewpoint of further improving the water absorption of the hardened body of the cement-containing composition. Also, the amount is 320 parts by mass or less, preferably 310 parts by mass or less, more preferably 280 parts by mass or less, and particularly preferably 260 parts by mass or less, from the viewpoint of further improving the abrasion resistance of the hardened body of the cement-containing composition.

[0016] The polymer for cement admixture used in the present invention may be any general polymer used as an admixture for cement, and examples thereof include acrylic polymers, styrene acrylic polymers, vinyl acetate polymers, butadiene polymers, and natural rubber polymers, etc. These may be used alone or in combination of two or more. Among these, from the viewpoint of ease of handling, etc., acrylic polymers and styrene-acrylic polymers are preferred, and acrylic polymers are more preferred. In addition, the glass transition temperature (Tg) of the polymer for admixture with cement is preferably less than 0° C., more preferably −20° C. or lower, even more preferably −30° C. or lower, and particularly preferably −40° C. or lower, from the viewpoint of improving adhesion and conformability to the substrate of the pavement when the cement-containing composition is used as a pavement repair material. The lower limit of the glass transition temperature is not particularly limited, but is preferably −70° C. from the viewpoint of ease of availability.

[0017] The form of the polymer for cement admixture used in producing the cement-containing composition of the present invention is not particularly limited, and may be either a dispersion or a powdered resin. More specifically, the polymer for cement admixture may be any of (i) a dispersion such as a rubber latex and a resin emulsion, and (ii) a powdered resin that can be re-emulsified, as specified in "JIS A 6203:2015 (polymer dispersions for cement admixture and re-emulsifiable powdered resins)". Among these, resin emulsions are preferred from the viewpoint of ease of handling. In this specification, the polymer for cement admixture does not include water. When the polymer for cement admixture is used in a form containing water such as an emulsion, the amount of the polymer for cement admixture excludes the amount of water contained in the emulsion. The content of the polymer for cement admixture (solid content) in the emulsion is preferably 30 to 70 mass %, more preferably 40 to 60 mass %.

[0018] The amount of the polymer for cement admixture per 100 parts by mass of cement is 18 to 62 parts by mass, preferably 19 to 61 parts by mass, more preferably 30 to 55 parts by mass, and particularly preferably 40 to 50 parts by mass. If the amount is less than 18 parts by mass, the adhesiveness and conformability of the cement-containing composition to the substrate such as a pavement will decrease. If the amount is more than 62 parts by mass, the water absorption of the hardened product of the cement-containing composition will decrease.

[0019] The amount of water per 100 parts by mass of cement is 170 to 300 parts by mass, preferably 180 to 290 parts by mass, more preferably 190 to 280 parts by mass, and particularly preferably 240 to 270 parts by mass or more. If the amount is less than 170 parts by mass, the water absorption of the hardened body of the cement-containing composition decreases. If the amount is more than 300 parts by mass, the wear resistance of the hardened body of the cement-containing composition decreases. When the polymer for cement admixture is used in a form containing water, such as an emulsion, the water contained in the emulsion is included in the above amount of water.

[0020] The cement-containing composition of the present invention may contain other materials as required within the scope of not impairing the object of the present invention. Examples of other materials that may be contained as required include various admixtures such as cement dispersants (water reducing agents, AE water reducing agents, high performance water reducing agents or high performance AE water reducing agents), hardening retarders, defoamers, and shrinkage reducing agents, as well as various admixtures such as fly ash, silica fume, and ground granulated blast furnace slag. The content of other materials in the cement-containing composition (the total content when multiple other materials are included) is preferably 20 mass % or less, more preferably 10 mass % or less, and particularly preferably 5 mass % or less.

[0021] Preferred physical properties of the cement-containing composition of the present invention are as follows: The water absorption rate of the hardened body of the cement-containing composition is preferably 25.0% or more, more preferably 28.0% or more, and particularly preferably 30.0% or more, from the viewpoint of absorbing more water from rainfall, etc., and preventing the formation of puddles on the surface of the pavement. In addition, from the viewpoint of further improving the abrasion resistance of the hardened body of the cement-containing composition, the water absorption rate is preferably 45.0% or less, more preferably 42.0% or less, and particularly preferably 40.0% or less. The water absorption rate can be calculated from the dry mass of the hardened body of the cement-containing composition (referred to as the "dry mass" in formula (1)) and the mass of the hardened body sufficiently immersed in water (also referred to as the "immersed mass" in formula (1)) using the following formula (1). {(immersed mass - dry mass) / dry mass}×100=water absorption rate (%) ···(1)

[0022] The flow value of the cement-containing composition before hardening is preferably 70 mm or more, more preferably 75 mm or more, even more preferably 78 mm or more, and particularly preferably 82 mm or more, as measured in accordance with "JASS 15 M-103," from the viewpoints of ease of application work using a trowel and filling of the repaired body into a recess that requires repair. In addition, from the viewpoints of preventing an excessive amount of water and further improving the water absorption of the hardened body of the cement-containing composition, the above flow value is preferably 200 mm or less, more preferably 180 mm or less, even more preferably 150 mm or less, and particularly preferably 120 mm or less.

[0023] Regarding the adhesion and conformability of the cement-containing composition, for example, a test specimen (pavement) having a base layer made of a dense-graded asphalt mixture and a surface layer made of a cement-containing composition on the upper surface of the base layer is used. The ratio of mortar aggregate fracture surfaces calculated from the fracture surfaces of the pavement using a Construction Research Institute-type tensile testing machine specified in "JIS A 6909:2014 (Architectural Finish Coating Materials)" can be used as an index. Of 100% of the fracture surfaces of the pavement, the proportion of mortar aggregate fracture surfaces is preferably 80% or more, more preferably 90% or more, and particularly preferably 95% or more. A large ratio indicates that the cement-containing composition has excellent adhesion and conformability. The abrasion loss (abrasion resistance against foot traffic, etc.) of the hardened body of the cement-containing composition is preferably 2.00 g or less, more preferably 1.90 g or less, even more preferably 1.80 g or less, and particularly preferably 1.50 g or less, as measured after 2,000 revolutions under a load of 250 g using a Taber abrasion tester and a GC-150H abrasion wheel in accordance with "JIS K 7204:1999 (Plastics - Abrasion test method based on abrasion theory)". The smaller the abrasion loss value, the better the abrasion resistance.

[0024] The cement-containing composition of the present invention can be used as a repair material to easily and quickly repair areas (e.g., recesses) of pavements (especially those made of dense-graded asphalt mixtures) that require repair. An example of a method for repairing a pavement surface using the cement-containing composition of the present invention includes a powdery composition preparation step of mixing cement, inorganic porous particles, and fine aggregate to obtain a powdery composition, a cement-containing composition preparation step of mixing the powdery composition, a polymer for admixture with cement, and water to prepare a cement-containing composition, and a filling step of filling and hardening the cement-containing composition into recesses in a pavement made of a dense-graded asphalt mixture that require repair. A pavement repaired by the above method, which contains a hardened body of a cement-containing composition and a hardened body of a dense-graded asphalt mixture, is less likely to develop puddles on its surface because the hardened body has excellent water absorption properties. In addition, instead of the powdery or granular composition preparation step and the cement-containing composition preparation step, a step of simultaneously mixing the materials to prepare the cement-containing composition may be provided. The cement-containing composition may also be used as a pavement material rather than as a repair material. Examples of pavements using the above-mentioned cement-containing composition include pavements made of the above-mentioned cement-containing composition, and pavements including a surface layer made of the above-mentioned cement-containing composition and a base layer made of a dense-graded asphalt mixture. EXAMPLES

[0025] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. [Materials used] (1) Cement: ultra-fast hardening cement, manufactured by Taiheiyo Cement Corporation, product name "Super Jet Cement" (2) Inorganic porous particles A; Zeolite, manufactured by Shin Tohoku Chemical Industry Co., Ltd., particles having a particle size of 0.5 mm or more and less than 1.0 mm: 50% by mass, particles having a particle size of 1.0 to 2.0 mm: 50% by mass (3) Inorganic porous particles B; Zeolite, manufactured by Shin Tohoku Chemical Industry Co., Ltd., particles having a particle size of 0.5 mm or more and less than 1.0 mm: 99% by mass or more (4) Inorganic porous particles C; Zeolite, manufactured by Shin Tohoku Chemical Industry Co., Ltd., particles having a particle size of 1.0 to 2.0 mm: 99% by mass or more (5) Fine aggregate: dried Kashima silica sand, particles with a particle size of 0.15 to 0.6 mm: 99% by mass or more (6) Polymer emulsion for cement mixing; containing 50% by mass of acrylic polymer in terms of solid content, Tg: -51°C, MFT (minimum film-forming temperature): 3°C or less, pH: 8.2, average particle size: 240 nm, clay: 310 mPa s (7) Set retarder: potassium sodium tartrate

[0026] [Examples 1 to 14] The cement-containing composition of the present invention was prepared by mixing (kneading) each material in the amounts (parts by mass) shown in Tables 1 and 2 with 0.3 parts by mass of a hardening retarder relative to 100 parts by mass of cement. In Tables 1 to 4, "polymer" refers to the solid content (acrylic polymer) contained in the polymer emulsion for cement admixture. The amount of water in Tables 1 to 4 includes the water contained in the polymer emulsion for cement admixture. The prepared cement-containing compositions were evaluated for the following physical properties as follows. (1) Water absorption rate In accordance with "JIS R 5201:2015 (Physical Testing Methods for Cement)", 40 x 40 x 160 mm test specimens were prepared and cured at room temperature for up to 7 days. After that, they were dried in a drying room at 60°C for 24 hours, and the mass (dry mass) of the test specimens was measured. Next, the test specimen was immersed in water for 24 hours, and the mass of the test specimen (immersed mass) was measured. The water absorption rate was calculated using the dry mass, the soaked mass, and the following formula (1). {(immersed mass - dry mass) / dry mass}×100=water absorption rate (%) ···(1) (2) Flow value In accordance with "JASS 15 M-103", the flow value was measured using a cylindrical cone with an inner diameter of φ50 mm and a height of 51 mm. (3) Adhesion (adhesion breakage status) The cement-containing composition was applied to the surface (upper surface) of the hardened dense-graded asphalt mixture (300 mm x 300 mm x 50 mm) so that the surface layer consisting of the cement-containing composition was 10 mm thick, and then the material was left to cure at room temperature for 7 days. A tensile test was conducted on the repaired portion of the pavement after curing (the hardened portion of the cement-containing composition) until fracture using the Construction Research Institute type tensile testing machine specified in "JIS A 6909:2014 (Architectural Finishing Coating Materials)". The percentage of the area of ​​the mortar aggregate fracture surface (surface fractured at the hardened part of the cement-containing composition) (shown as "mortar aggregate" in Tables 2 to 4) and the percentage of the area of ​​the interface fracture surface (surface fractured at the interface between the hardened part of the cement-containing composition and the hardened part of the dense-graded asphalt mixture) (shown as "interface" in Tables 2 to 4) were calculated out of the total area of ​​the fracture surface of the pavement after fracture. Note that the larger the area of ​​the mortar aggregate fracture surface and the smaller the area of ​​the interface fracture surface, the better the adhesion.

[0027] (4) Abrasion resistance In accordance with "JIS K 7204:1999 (Plastics - Abrasion test method based on abrasion theory)", a Taber abrasion tester and a GC-150H abrasion wheel were used to measure the abrasion loss after 2,000 revolutions under a load of 250g. The results are shown in Tables 1 and 2.

[0028] [Table 1]

[0029] [Table 2]

[0030] [Comparative Example 1] A cement-containing composition was prepared in the same manner as in Example 1, except that no inorganic porous particles were used and each material was used in the amounts shown in Tables 3 and 4. [Comparative Examples 2 to 6] A cement-containing composition was prepared in the same manner as in Example 1, except that no fine aggregate was used and each material was used in the amounts shown in Tables 3 and 4. [Comparative Examples 7 to 17] A cement-containing composition was prepared in the same manner as in Example 1, except that the materials in the amounts shown in Tables 3 and 4 were used. The physical properties, such as the water absorption rate, of each of the cement-containing compositions prepared in Comparative Examples 1 to 17 were calculated in the same manner as in Example 1. The results are shown in Tables 3 and 4. In addition, in the measurement of the flow value of Comparative Example 15, material separation was observed in the cement-containing composition.

[0031] [Table 3]

[0032] [Table 4]

[0033] From Tables 1 to 4, it can be seen that the hardened product of the cement-containing composition of the present invention has a water absorption rate of 25% or more and a flow value before hardening of 70 mm or more, and therefore has excellent water absorption, workability, and filling ability into recesses. It can also be seen that it has excellent adhesion and abrasion resistance.

Claims

1. A cement-containing composition comprising cement, inorganic porous particles, fine aggregate, a polymer for cement admixture, and water, The inorganic porous particles have a particle size distribution in which the content of particles having a particle size of 0.5 mm or more and less than 1.0 mm is 40 to 60 mass %, and the content of particles having a particle size of 1.0 to 2.0 mm is 40 to 60 mass %, A cement-containing composition, characterized in that, relative to 100 parts by mass of the cement, the amount of the inorganic porous particles is 150 to 420 parts by mass, the amount of the fine aggregate is 180 to 320 parts by mass, the amount of the polymer for admixture with cement is 18 to 62 parts by mass, and the amount of the water is 170 to 300 parts by mass.

2. 2. The cement-containing composition according to claim 1, wherein said inorganic porous particles are zeolite.

3. 2. The cement-containing composition according to claim 1, wherein the fine aggregate has a particle size distribution in which the content of particles having a particle size of 0.15 to 0.6 mm is 90 mass % or more.

4. 2. The cement-containing composition according to claim 1, wherein the polymer for cement admixture is at least one selected from the group consisting of acrylic polymers and styrene-acrylic polymers.

5. 2. The cement-containing composition according to claim 1, wherein the water absorption rate of the hardened product of said cement-containing composition is 25.0% or more.

6. A pavement comprising a hardened product of the cement-containing composition according to any one of claims 1 to 5 and a hardened product of a dense-graded asphalt mixture.

7. A method for repairing a pavement using the cement-containing composition according to any one of claims 1 to 5, a powdery or granular composition preparation step of mixing the cement, the inorganic porous particles, and the fine aggregate to obtain a powdery or granular composition; a cement-containing composition preparation step of mixing the powdery or granular composition, the polymer for cement admixture, and the water to prepare the cement-containing composition; A filling step of filling and hardening the cement-containing composition into a recess in a pavement including a hardened dense-graded asphalt mixture that requires repair; A method for repairing a pavement, comprising:

Citation Information

Patent Citations

  • Programmable controller system

    JP1989066701A

  • Method for repairing concrete slab-asphalt pavement road surface and polymer cement mortar

    JP2013234489A